Investigating the variations in survival rates for very preterm infants in 10 European regions: the MOSAIC birth cohort. Issue 3 (19th September 2008) - Draper, E S; Zeitlin, J; Fenton, A C; Weber, T; Gerrits, J; Martens, G; Misselwitz, B; Breart, G
Abstract : Objective: To investigate the variation in the survival rate and the mortality rates for very preterm infants across Europe. Design: A prospective birth cohort of very preterm infants for 10 geographically defined European regions during 2003, followed to discharge home from hospital. Participants: All deliveries from 22 + 0 to 31 + 6 weeks' gestation. Main outcome measure: All outcomes of pregnancy by gestational age group, including termination of pregnancy for congenital anomalies and other reasons, antepartum stillbirth, intrapartum stillbirth, labour ward death, death after admission to a neonatal intensive care unit (NICU) and survival to discharge. Results: Overall the proportion of this very preterm cohort who survived to discharge from neonatal care was 89.5%, varying from 93.2% to 74.8% across the regions. Less than 2% of infants <24 weeks' gestation and approximately half of the infants from 24 to 27 weeks' gestation survived to discharge home from the NICU. However large variations were seen in the timing of the deaths by region. Among all fetuses alive at onset of labour of 24–27 weeks' gestation, between 84.0% and 98.9% were born alive and between 64.6% and 97.8% were admitted to the NICU. For babies <24 weeks' gestation, between 0% and 79.6% of babies alive at onset of labour were admitted to neonatal intensive care. Conclusions: There are wide variations in the survival rates to discharge from neonatal intensive care for very preterm deliveries and in the timing of death across the MOSAIC regions. In order to directly compare international statistics for mortality in very preterm infants, data collection needs to be standardised. We believe that the standard point of comparison should be using all those infants alive at the onset of labour as the denominator for comparisons of mortality rates for very preterm infants analysing the cohort by gestational age band.